What Makes Teacher Preparation Legitimate? An Analysis of Teacher Residency Websites. (3rd April 2021) - Reagan, Emilie Mitescu; Ahn, Joonkil; Roegman, Rachel; Vernikoff, Laura
ABSTRACT: As teacher residency programs are housed in universities, charter networks, nonprofit organizations, school districts, and museums, they form a model ripe for analysis. In this study, we conduct a content analysis of a random sample of 20 teacher residency program websites, focusing on each program's stated purpose, structures, and attributes. Drawing on institutional theory, we analyze the claims of legitimacy made by residency programs. Findings suggest that the 20 residency programs sampled for the study exhibit structural similarities to each other, yet they make different types of legitimacy claims. Key features of residency programs include explicit district and school partners, concurrent graduate coursework, and yearlong clinical experience. However, claims to legitimacy tend to be based on a variety of reasonings and potential values, including legitimacy by innovation, legitimacy by association, and legitimacy by data. We identify organizations and institutions that may influence the residency model, and we offer implications for the teacher residency model and the field of teacher preparation.